Echoic Teaching and Vocalization Accuracy in Picture Naming Tasks for Children with Hearing Loss (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Speech distortions are observed in children with hearing loss (HL). This study verified whether teaching echoic was linked to conditional discrimination tasks in a reading teaching program and whether it would increase speech accuracy in three children with HL. The equivalence-based program taught 51 words via computer in discrete trials. Discriminations between dictated and written words, their smaller units (syllables and letters), and figures were trained by the matching-to-sample (selecting a printed figure/word/syllable conditionally to the dictated word/syllable) and constructed-response procedures matching-to-sample (select letters in sequence conditionally to the dictated/printed word). The echoic was linked to matching-to-sample, in two of four teaching units, balancing the conditions between the participants. Periodic probes monitored speech. In the pre-tests, naming was below 60% and reading was above 66% correct; they learned echoic, and naming improved in all teaching units, regardless of echoic teaching.
Keywords: Echoic Teaching; Reading Teaching; Hearing Impairment.